Dignity therapy for non-terminally ill elderly - Miguel Julião; Fernanda Barata (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2020)
Dignity Therapy (DT) is a psychotherapeutic approach designed to increase patient's sense of meaning and purpose, offering the opportunity to talk about issues that matter most to them, to share moments they feel were most important and to speak of things they would like to be remembered [1]. DT has been developed and trialled for those near death and had shown efficacy on several psychosocial outcomes [1,2]. However, some recent case reports have been published about the use of DT in non-terminal ill patients with mental disorders such as major depressive disorder and alcohol use disorder [3-5].